If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 4(2) * f(a) + 2 Multiply 4 * 2 y = 8f * a + 2 Multiply f * a y = 8af + 2 Reorder the terms: y = 2 + 8af Solving y = 2 + 8af Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 2 + 8af
| y=4(a+3)+2 | | 2y=4(4/5)-2 | | y=4(2x)+2 | | 9y^2-12y+121=0 | | 2n^2+2n=1 | | (v+7)(v-4)= | | 2z-20=29+9z | | 5z-11=3+7z | | 5p-20=31-3p | | x^2+4x+3x^2-2x= | | 7p-4=-8+9p | | 4z+5x-10y=100 | | -8(2t+2)=-16 | | 3(f-2)=-9 | | -10(s+2)=-79 | | 47=6x+5 | | 3x^3=18x^2+21x | | 5(t+2)=-10 | | h(x)=3x-2 | | 100=0.2^2/2 | | 3(3s+1)=75 | | 3(2l+6)=60 | | 42*x+50=26*x+76 | | (u+4)*10=90 | | 5x-35x^2=0 | | (q-6)*6=12 | | x^2+3xy-4y^2-12+x=0 | | tanx=31 | | 256x^2+81x^2=22 | | 7x+20=3x-4 | | 100y+500=1000-200y | | 2y^2-4y=o |